Graduate University EFL Learners’ Perceptions on Peer Assessment in Improving Speaking Skills - Kristian Florensio Wijaya (ELITE Association Indonesia, 2022)
Responding to this ever-changing era, graduate university EFL learners are highly demanded to master speaking skills to be labeled as proficient target language academicians. However, the journey to attain advanced mastery of this communicative competence is a tough one since they frequently experience unpleasant speaking learning activities in their daily routines. Peer assessment appeared as one of the effective solutions to overcome the aforementioned hindrance by which graduate university EFL learners can constantly experience more enjoyable speaking learning dynamics in the support of meaningful, constructive, and encouraging feedback addressed by their trusted learning companions. This present small-scale qualitative study set out to profoundly investigate graduate university EFL learners’ perceptions of peer assessment in improving speaking skills. To this end, 10 Likert-scale online questionnaire items and 5 open-ended written narrative inquiry questions were distributed to 21 English Education Master Students batch 2020 graduating from one of the private universities in Yogyakarta. Based on the research results a vast majority of graduate university EFL learners highly support the continual integration of peer assessment in nowadays speaking learning activities due to the promotion of fruitful speaking learning outcomes and meaningful internal as well as external supports. Some recent recommendations were also provided for the betterment of speaking learning investigation. Keywords: Peer assessment, speaking skills, EFL learners